2010
DOI: 10.1089/jpm.2010.0082
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Factors that Influence Informal Caregiving in Medication Management for Home Hospice Patients

Abstract: Objective: To explore factors that influence how informal caregivers manage medications as part of caring for hospice patients. Methods: Semistructured, open-ended interviews were conducted with 23 informal caregivers and 22 hospice providers from 4 hospice programs in the Chicago metropolitan areas. Qualitative analysis was conducted consistent with the grounded theory approach. Results: In general, informal caregivers and hospice providers identified similar key factors that facilitated or impeded caregivers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
59
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(66 citation statements)
references
References 19 publications
(16 reference statements)
4
59
0
3
Order By: Relevance
“…13,14 Informal caregivers may often feel uncomfortable or ill equipped to manage patients' symptoms at home. [13][14][15][16] Given that caregiving and symptom management are likely intertwined components of quality home hospice care, hospitalization may signify the fact that certain caregivers require more support. Research studying symptom management interventions in the home hospice setting is still sparse; however, interventions that incorporate new technologies or empower caregivers through education have had promising results.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 Informal caregivers may often feel uncomfortable or ill equipped to manage patients' symptoms at home. [13][14][15][16] Given that caregiving and symptom management are likely intertwined components of quality home hospice care, hospitalization may signify the fact that certain caregivers require more support. Research studying symptom management interventions in the home hospice setting is still sparse; however, interventions that incorporate new technologies or empower caregivers through education have had promising results.…”
Section: Discussionmentioning
confidence: 99%
“…A significant concern is that caregiver fatigue could be associated with negative patient outcomes. For example, a fatigued caregiver may be more likely to make a medication administration error (Lau et al, 2010). Another study revealed that patient fatigue is associated with lost work hours and may have broader economic repercussions because of negative influence on the caregiver's ability to work.…”
Section: Discussionmentioning
confidence: 99%
“…depending on their socio-economic status, literacy, personality traits, resilience, and contingent factors [95,96].…”
Section: Discussionmentioning
confidence: 99%